2014
DOI: 10.1007/s10482-014-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytisus villosus from Northeastern Algeria is nodulated by genetically diverse Bradyrhizobium strains

Abstract: Fifty-one rhizobial strains isolated from root nodules of Cytisus villosus growing in Northeastern Algeria were characterized by genomic and phenotypic analyses. Isolates were grouped into sixteen different patterns by PCR-RAPD. The phylogenetic status of one representative isolate from each pattern was examined by multilocus sequence analyses of four housekeeping genes (16S rRNA, glnII, recA, and atpD) and one symbiotic gene (nodC). Analysis of 16S rRNA gene sequences showed that all the isolates belonged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The NI values among the strains from our study and related type strains ranged from 99.4 to 99.9 % (). The results agree with several reports that the 16S rRNA sequences are highly conserved in the genus Bradyrhizobium , with many species sharing more than 99 % NI, not allowing proper evolutionary information [7, 12, 13, 34].…”
Section: Phylogenysupporting
confidence: 90%
“…The NI values among the strains from our study and related type strains ranged from 99.4 to 99.9 % (). The results agree with several reports that the 16S rRNA sequences are highly conserved in the genus Bradyrhizobium , with many species sharing more than 99 % NI, not allowing proper evolutionary information [7, 12, 13, 34].…”
Section: Phylogenysupporting
confidence: 90%
“…(i) Symbiovar genistearum was described by Vinuesa et al (45) and includes many strains nodulating a large number of plants from the tribe Genisteae, including the genera Lupinus, Cytisus, Retama, Chamaecytisus, and Spartium, growing in Africa, Europe, and America (12,33,39,40,45). The majority of L. micranthus-associated isolates related to B. lupini (group I), and those similar to B. cytisi/B.…”
Section: Discussionmentioning
confidence: 99%
“…lupini and B. cytisi/B. rifense lineages and to symbiovar genistearum (16,33,52). Importantly, these microorganisms may be dominant in neutral or acidic soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. and B. rifense sp. nov. in Morocco [39,40] and by genetically diverse Bradyrhizobium strains in Algeria belonging to B. japonicum and B. canariense and to new lineage within the Bradyrhizobium genus [41]. Fiftytwo strains isolated from root nodules of the Moroccan shrubby legume Cytisus triflorus were genetically characterized, and results showed that it is nodulated by Bradyrhizobium strains, with 99% homology with Bradyrhizobium genosp.…”
Section: The Genus Bradyrhizobium (Bradyrhizobiaceae)mentioning
confidence: 99%